Indeterminism in Kane’s Event-Causal Libertarianism - Robert J Nowell (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2014)
In this paper, I examine the plausibility of event-causal libertarianism, a prominent view on free will which regards indeterminism in the causal history of a decision as necessary for an agent’s moral responsibility for a subsequent action. Specifically, I investigate how Robert Kane’s event-causal libertarian account fares in light of Derk Pereboom’s powerful “disappearing agent” objection, in addition to criticisms of my own. Kane concludes that Pereboom’s objection is ineffective against his account. I argue against Kane’s conclusion by highlighting a dilemma which results from Kane's response to the disappearing agent objection; either way Kane’s position is interpreted, his account is unsuccessful.
Keywords: Free Will; indeterminism; Kane; Pereboom; action; decision; event-causal libertarianism; determinism; disappearing agent; moral responsibility; plural voluntary control